Development of a Cloud-Based Simulation Measurement Laboratory and Evaluation System based on Unity3D - Liang, Xiaoyang (International Journal of Mechanical and Electrical Engineering, 2025)
This paper presents the development of a virtual simulation teaching platform for measuring equipment in the mechanical industry, aimed at improving students’ learning effectiveness and operational skills. Traditional teaching methods relying on physical hardware are costly and pose safety risks, while the virtual simulation platform offers a safe, repetitive, and resource-efficient learning environment. The platform is divided into four modules: measuring tool cognition, measuring tool experiment, measuring tool evaluation, and user management. Each module is meticulously designed to meet specific teaching and evaluation needs, covering everything from basic knowledge learning to practical skill development. By achieving the outlined objectives, this platform will contribute to the technological advancement and talent cultivation in the mechanical manufacturing industry, promoting the sustainable development of the industry.